A DNAzyme-based label-free fluorescent probe for guanosine-5′-triphosphate detection. Issue 21 (27th August 2020) - Hu, Chengzhen; Jiang, Kemei; Shao, Zihao; Shi, Minqing; Meng, Hong-Min
Abstract : A DNAzyme-based fluorescent probe with self-phosphorylation ability for label-free and sensitive GTP detection in buffer and human serum samples. Abstract : Guanosine-5′-triphosphate (GTP) plays a key role in many important biological processes of cells. It is not only a primer for DNA replication and one of the four essential nucleoside triphosphates for mRNA synthesis, but also an energy source for translation and other important cellular processes. It can be converted to adenine nucleoside triphosphate (ATP), and the intracellular GTP level is closely related to the specific pathological state, so it is crucial to establish a simple and accurate method for the detection of GTP. Deoxyribozymes have unique catalytic and structural properties. One of the deoxyribozymes which is named DK2 with self-phosphorylation ability can transfer a phosphate from GTP to the 5′ end in the presence of manganese(ii ), while lambda exonuclease ( λ exo ) catalyzes the gradual hydrolysis of double-stranded DNA molecules phosphorylated at the 5′-end from 5′ to 3′, but cannot cleave the 5′-OH end. The fluorescent dye SYBR Green I (SG I) can bind to dsDNA and produce significant fluorescence, but it can only give out weak fluorescence when it is mixed with a single strand. Here, we present a novel unlabeled fluorescence assay for GTP based on the self-phosphorylation of deoxyribozyme DK2 and the specific hydrolysis of λ exo . Owing to the advantages of simple operation, high sensitivity, good specificity, low cost and without fluorophore (quenching group) labeling, this method has great potential in biological applications.